An integrated solution for waste heat recovery from fuel cells applied to adsorption systems. (25th May 2018) - Oro, Marcos Vinício; de Oliveira, Rogério Gomes; Bazzo, Edson
Highlights: Analysis of a system composed of a PEM fuel cell and a chemisorption chiller. Adsorption chiller energized by heat rejection from fuel cells. Thermosyphon as solution to integrate fuel cells and adsorption chillers. Thermosyphon for fuel cell controlling and energization of adsorption chillers. Fuel cells integrated to adsorption chillers producing electricity and cooling power. Abstract: Fuel cells have been widely studied and proposed as a promising alternative in the automobile industry, distributed generation, and other industrial applications. Therefore, a cogeneration scheme to produce electricity and cooling power is analyzed with the aid of a numeric simulation, considering the possibility of using the heat rejected by a proton exchange membrane fuel cell (PEMFC) to drive a chemisorption chiller. The chiller employed ammonia as refrigerant and NaBr impregnated in expanded graphite as adsorbent. The thermal energy integration between the chemisorption system and the PEMFC was accomplished by a thermosyphon, which acted as a heat reservoir to reduce the temperature drop in the PEMFC stack. Experimental results were used to validate the simulation of the adsorbent behavior, and the PEMFC operation was simulated from a dynamic model available in the literature. The fuel cell stack fueled by hydrogen, the bed length of chiller reactors and the amount of working fluid used in the thermosyphon heat reservoir are considered in the analysis. For fuel cell power outputs in the range of 600–1400 W, cooling powers up to 400 W were found. This increases the useful energy of the hydrogen, with overall efficiencies up to 63%.